Implementasi Musik Ilustrasi Film Animasi Hybrid "Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain" Menggunakan Teknik Leitmotif - Vigho Antonio; Fris Okta Falma (AHKAM, 2026)
Although film music has been used to bind narratives in culturally themed animated films, the application of the leitmotif technique in hybrid animation featuring Tingkuluak remains limited. This study aimed to describe and analyze the implementation of the leitmotif technique in the film score of the animated film Tingkuluak: Pusaka Perempuan Minang dalam Sehelai Kain. The study employed a qualitative descriptive approach with a practice-based research design encompassing the preproduction, production, and postproduction stages. Data were collected through questionnaires administered to young people, an interview with a cultural informant, a literature review, documentation of the creative process, alpha testing, and beta testing with an animation expert. The data were analyzed descriptively by categorizing musical requirements, interpreting audiovisual compatibility, and conducting technical evaluations. The results showed that leitmotifs developed through variations in melody, harmony, tempo, dynamics, instrumentation, and sound layering were able to establish a musical identity, reinforce the atmosphere, and maintain narrative continuity. The use of MIDI, virtual instruments, talempong, and Malay flute further accentuated the nuances of Minangkabau culture. The testing results also indicated the need to improve the consistency of dialogue volume, the alignment of the music with the emotions of the scenes, and audiovisual synchronization. This study enriches the practice of creating film music based on local culture and offers a film-scoring production workflow that can be applied to the development of educational animation media.